UPAYA PENERAPAN METODE LEAN THINKING PADA PROSES PELAYANAN FARMASI RAWAT JALAN - Komang Adhi Restudana; Gede Sri Darma (STIE Mandala Jember, 2022)
Pharmacy services in a hospital are an inaccessible part of the hospital services as a whole. The accumulation of prescriptions in the pharmacy will cause the prescription process to be long and long, which has an impact on customer waiting times, which of course will have a major impact on customer satisfaction. From the standard time set as Quality Indicators at Bali Jimbaran Hospital, namely: drug processing at the outpatient pharmacy of Bali Jimbaran Hospital is 60 minutes of concocted drugs, 30 minutes of non-concocted drugs. The purpose of this research is to identify activities starting from the input, process and results generated through the Lean approach. The method used is an observational action process research, using lean methods to photograph the outpatient pharmacy service process flow through document review, direct interviews, interviews. The result of the research is an improvement in waiting time, it can be seen that the NVA activities can be eliminated by 66% and VA activities show an increase of 44%. With the many activities that are VA and the elimination of NVA activities, it will accelerate the process of outpatient pharmacy services at the Bali Jimbaran Hospital and improve customer satisfaction, which can be seen from the decrease in customer complaints against outpatient pharmacy services by up to 50%, which was previously 80%. Keywords: Lean, Pharmacist, Waiting time, Value Added, Non-Value Added